High-throughput production of human proteins for crystallization: the SGC experience. - Savitsky, P; Bray, J; Cooper, C; Marsden, B; Mahajan, P; Burgess-Brown, N; Gileadi, O (Elsevier, 2010)
Producing purified human proteins with high yield and purity remains a considerable challenge. We describe the methods utilized in the Structural Genomics Consortium (SGC) in Oxford, resulting in successful purification of 48% of human proteins attempted; of those, the structures of approximately 40% were solved by X-ray crystallography. The main driver has been the parallel processing of multiple (typically 9-20) truncated constructs of each target; modest diversity in vectors and host systems; and standardized purification procedures. We provide method details as well as data on the properties of the constructs leading to crystallized proteins and the impact of methodological variants. These can be used to formulate guidelines for initial approaches to expression of new eukaryotic proteins.